JURIDICAL REVIEW OF THE MERAH PUTIH COOPERATIVE AND THE ROLE OF THE NOTARY MAKING THE COOPERATIVE DEED (NPAK) IN ITS ESTABLISHMENT BASED ON INDONESIAN COOPERATIVE LAW - Felly Faradina; Zulhendrawan; Dini Dewi Heniarti; Neni Sri Imaniyati; Dhody Ananta Rivandi W (RADJA PUBLIKA, 2025)
As a manifestation of the implementation of Article 33 paragraphs (1) and (4) of the 1945 Constitution of the Republic of Indonesia, the government initiated a community economic empowerment program in early 2025 through the establishment of the